(untitled) (Ustozlar uchun, 2025)
Abstract This article explores modern approaches to teaching geometry within the STEAM (Science, Technology, Engineering, Art, Mathematics) educational framework. It emphasizes the importance of interdisciplinary teaching, the use of modern digital tools, and the development of students’ creative and analytical thinking skills through geometric education.